Design of Automatic Fish Feeding in Arduino-Based Catfish Farming - Sujono, Sujono; Azha, Atika Chaula (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This Arduino-based fish feed aims to design and build a catfish feeder automatically based on the Arduino Uno-based fish feeding schedule. This feeder uses the RTC DS3231 to set the time and schedule for feeding fish which is equipped with a Servo Motor as a feed valve opener and an LCD as a clock and date display on the feed schedule. The weight of the feed issued is based on the weight of the catfish and the number of fish. The number of catfish in this study is 100 fish with a pond size of 2 meters by 2 meters. The scheduled feeding schedule is morning, afternoon, evening and night, depending on the age of the catfish. Considering that catfish are cannibals that eat their own kind and are nocturnal, that is, animals that are active at night and sleep during the day, it is best if some of the feed is given more in the afternoon or at night because the catfish's appetite is high at night. The feeding schedule is in the morning at 08.00, noon at 12.00, in the afternoon at 16.00 and at night at 20.00. The button on the remote will control how many times the feed will come out of the feed tray. When the feed in a fish feed container has run out, the ultrasonic sensor will work and an alarm will sound from the buzzer which sounds as a reminder. From the test results, it was obtained that the feed weight was regular after designing an Arduino Uno-based automatic fish feed structure, and the servo moved according to a predetermined schedule.